2003
DOI: 10.1093/nar/gkg266
|View full text |Cite
|
Sign up to set email alerts
|

The enzymatic basis of processivity in lambda exonuclease

Abstract: Lambda exonuclease is a highly processive 5'-->3' exonuclease that degrades double-stranded (ds)DNA. The single-stranded DNA produced by lambda exonuclease is utilized by homologous pairing proteins to carry out homologous recombination. The extensive studies of lambda biology, lambda exonuclease enzymology and the availability of the X-ray crystallographic structure of lambda exonuclease make it a suitable model to dissect the mechanisms of processivity. lambda Exonuclease is a toroidal homotrimeric molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
123
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(141 citation statements)
references
References 25 publications
17
123
0
1
Order By: Relevance
“…Some of these phages encode a homolog of ParB, an enzyme important for DNA binding and segregation (26), as previously pointed out by Aravind's group (7) (e.g., Mycobacteriophage Rosebush). Other phages encode potential helicases and nucleases near the preQ 0 cluster [e.g., Gp11 of 9g and Gp39 of JenKI contain SnfII-like domains (39), Gp11 of Dp-1 is a RecU-like protein (40), Gp40 of JenK1 encodes a putative exonuclease (41), and Gp10 of Dp-1 is a Cas4-like protein (42); SI Appendix, Fig. S12].…”
Section: The Dpd Cluster Is Horizontally Transferred and Found In Genmentioning
confidence: 99%
“…Some of these phages encode a homolog of ParB, an enzyme important for DNA binding and segregation (26), as previously pointed out by Aravind's group (7) (e.g., Mycobacteriophage Rosebush). Other phages encode potential helicases and nucleases near the preQ 0 cluster [e.g., Gp11 of 9g and Gp39 of JenKI contain SnfII-like domains (39), Gp11 of Dp-1 is a RecU-like protein (40), Gp40 of JenK1 encodes a putative exonuclease (41), and Gp10 of Dp-1 is a Cas4-like protein (42); SI Appendix, Fig. S12].…”
Section: The Dpd Cluster Is Horizontally Transferred and Found In Genmentioning
confidence: 99%
“…DNA fragments larger than 3 kb also place a limit on Red mediated ssDNA processing, which is most efficient up to 3 kb 30 . Insertion cassettes exceeding 3 kb are dual resected and recombine less efficiently via a beta independent pathway 20 .…”
Section: Discussionmentioning
confidence: 99%
“…A few samples also contained incorrectly gap repaired (lane 2) or mistargeted plasmids (lanes 4 and 5). The failure of concurrent subcloning and targeting in some SPI recombinants highlights the limits of efficient SPI cloning when using large cassettes (> 3 kb), which arise from the constraints on Red processivity of long DNA fragments 30 , or if using short HA. Indeed, increasing the HA of the eYFP cassette to 200 bp increased SPI efficiency and the correct targeting of the cassette (data not shown).…”
Section: Knockin Vectorsmentioning
confidence: 99%
“…We have tested our methodology with a variety other enzymes such as BsmBI and BciVI and the quality and accuracy of the ssDNA molecules generated after the lambda exonuclease treatment was similar to those LPPs used in this study (data not shown). It is likely that this method can be used to produce very large single-stranded molecules, because lambda exonuclease is a very processive enzyme (32,33). Our method of producing singlestranded molecules has a number of applications where variable sizes or large quantities of long ssDNA molecules are needed.…”
Section: Discussionmentioning
confidence: 99%